The Implicit Relational Assessment Procedure (IRAP) as a measure of harm avoidance and incompleteness in obsessive-compulsive disorder - Vella, Kristina (2017)
Studies investigating harm avoidance and incompleteness in obsessive-compulsive disorder (OCD) have been limited to the use of questionnaire measures and behavioural tasks. Despite their utility, these methodologies are unable to capture cognitions that are not readily accessible through introspection or that are difficult to articulate, as they operate on a more visceral level. The current study explored harm avoidance and incompleteness using an implicit measure, the Implicit Relational Assessment Procedure (IRAP). Three behavioural tasks based on the main symptom dimensions (contamination/washing, checking, symmetry/ordering) and a series of self-report measures were used for comparative and validation purposes. The group with high obsessive-compulsive tendencies demonstrated no negative bias towards harm avoidance/incompleteness–related stimuli. No associations were identified between scores on the implicit measure and the explicit measures (questionnaires and behavioural task). The findings are interpreted in the light of extant literature with reference to the limitations of the current study.